IgA nephropathy pathogenesis and therapy: Review & updates. Issue 48 (2nd December 2022) - Habas, Elmukhtar; Ali, Elrazi; Farfar, Khalifa; Errayes, Mahdi; Alfitori, Jamal; Habas, Eshrak; Ghazouani, Hafedh; Akbar, Raza; Khan, Fahim; Al Dab, Aisha; Elzouki, Abdel-Naser
Abstract : Background: IgA nephropathy (IgAN) is the most frequent type of primary glomerulonephritis since the first type was described more than four decades ago. It is the prevalent cause of primary glomerular disease that causes end-stage renal disease. In most patients with IgAN, hematuria is the most common reported symptom, particularly in those with a preceding upper respiratory tract infection. Although the pathogenesis of IgAN is usually multifactorial, autoimmune complex formation and inflammatory processes are the most widely recognized pathogenic mechanisms. Multiple approaches have been trialed as a therapy for IgAN, including tonsillectomy, steroids, other immune-suppressive therapy in different regimens, and kidney transplantation. Aim and method: PubMed, Google, Google Scholar, Scopus, and EMBASE were searched by the authors using different texts, keywords, and phrases. A non-systemic clinical review is intended to review the available data and clinical updates about the possible mechanism(s) of IgAN pathogenesis and treatments. Conclusion: IgAN has a heterogeneous pattern worldwide, making it difficult to understand its pathogenesis and treatment. Proteinuria is the best guide to follow up on the IgAN progression and treatment response. Steroids are the cornerstone of IgAN therapy; however, other immune-suppressive and immune-modulative agents are used with a variable response rate. Kidney transplantation is highly advisable for IgAN patients, although the recurrence rate is high. Finally, IgAN management requires collaborative work between patients and their treating physicians for safe long-term outcomes.